MAKING CHILDREN LAUGH: PARENT–CHILD DYADIC SYNCHRONY AND PRESCHOOL ATTACHMENT. Issue 5 (25th August 2014) - Bureau, Jean‐FrançOis; Yurkowski, Kim; Schmiedel, Sabrina; Martin, Jodi; Moss, Ellen; Pallanca, Dominique; Bocknek, Erika L.; Hossain, Ziarat; Roggman, Lori
ABSTRACT The current study examined whether dyadic synchrony of father–child and mother–child interactions in a playful context were associated with attachment organization in preschool children. One hundred seven children (48 boys, Mage = 46.67 months, SD = 8.57) and their mothers and fathers (counterbalanced order of lab visits) participated in a playful interaction without toys (Laughing Task procedure). Playful interactions were coded based on the degree to which the dyads demonstrated a variety of behavior representing dyadic synchrony and task management. Children's attachment behavior toward fathers and mothers was observed in a modified separation–reunion procedure adapted for the preschool period. Results demonstrate that mothers and fathers are similar in their effort to arouse and engage their child in a playful context, but mothers achieved a greater synchrony with their child. Disorganized attachment to either mother or father is linked with a lack of synchrony in dyadic interaction. Findings are in contrast with prevailing theory, suggesting that despite gender‐related differences in parental playful behaviors, dyadic synchrony is equally important in both mother– and father–child relationships for the development of organized social and affectional bonds.